Peningkatan Hasil Belajar Potensi Kemaritiman Indonesia Melalui Model Pembelajaran Group Investigation - Susi Agustini (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study aims to improve student learning outcomes in the material of Indonesian maritime potential for class VII G students of SMP Negeri 1 Cibadak by using the Group Investigation learning model. This type of research is Classroom Action Research which is conducted in two cycles, each of which has four components, namely planning, implementing action, observing, and reflecting. The results showed that the application of the Group Investigation learning model can improve activity and learning outcomes in the material of Indonesian maritime potential for class VII G students of SMP Negeri 1 Cibadak. This can be seen from the average percentage of student learning activities in the first cycle of 58.75%, an increase of 24.37% in the second cycle to 83.12%. Likewise, learning outcomes have increased, it can be seen that the average learning outcomes in the first cycle of 64.84 increased 5.25 in the second cycle to 76.72.